Transvaginal four‐dimensional hysterosalpingo‐contrast sonography: Pain perception and factors influencing pain severity. Issue 1 (26th October 2020) - Zhang, Ning; Liu, Yu; He, Yanni; Shi, Jiayao; Zhou, Meijun; Liu, Hongmei
Abstract: Aim: The purpose is to investigate pain perception during transvaginal four‐dimensional hysterosalpingo‐contrast sonography (TV 4D‐HyCoSy) and factors influencing pain severity. Methods: This was a retrospective study included 340 women who underwent TV 4D‐HyCoSy examination from January 2016 to October 2017. The factors were recorded, including age, childbearing history, infertility type, history of pelvic inflammation, pelvic surgery, history of uterine manipulation, history of ectopic pregnancy, atropine delivery mode, uterine position, uterine malformation, uterine lesion, fibroid, intrauterine adhesion, polycystic ovary, endometrial implantation cyst, dysmenorrhea score, the degree of patency of fallopian tube and contrast agents dosage. Pain was evaluated during and after TV 4D‐HyCoSy. The time point of peak pain was evaluated and the influencing factors of moderate/severe pain were analyzed. Results: The highest pain occurred at contrast instillation. The independent influencing factors of moderate/severe pain were age ( P = 0.021), dysmenorrhea score ( P = 0.003) and tubal patency ( P < 0.001). Further analysis showed that age affected the pain score when TV 4D‐HyCoSy started and the peak pain occurred. Dysmenorrhea score and tubal patency affect the pain score at most time points. Conclusion: Age, dysmenorrhea score and tubal patency are factors influencing the severity of pain during TV 4D‐HyCoSy.